Autofluorescence spectroscopy of a human gastrointestinal carcinoma cell line - design of optical sensors for the detection of early stage cancer - Ferreira, D. S. (2009)
Human tissues show autofluorescence (AF) emission spectra when excited by ultraviolet or shortwavelength visible light. The intensity and shape of these spectra are dependent on the tissues pathological state and, therefore, its measurement gives information about the degree of malignant transformations that could lead to cancer. In this article, it is characterized the AF spectra of one human gastrointestinal carcinoma cell line (CACO-2). The obtained results showed significant AF signal for the presence of amino acids. The spectral information obtained can be used for the design of fluorescence optical sensors that will be incorporated on an endoscopic capsule, for measuring the AF emission spectra of normal and cancer cells. This integrated optical system will innovate on the diagnosis of early stage cancer.